Joint bleeds increase the inhibitor response to human factor VIII in a rat model of severe haemophilia A. (21st July 2016) - Lövgren, K. M.; Søndergaard, H.; Skov, S.; Wiinberg, B.
Abstract : Introduction: The most serious complication in haemophilia A (HA) replacement therapy with coagulation factor VIII (FVIII) is neutralizing antibodies, i.e. inhibitors. It has been hypothesized that danger signals generated during a bleed might have an adjuvant effect on the immune response to FVIII in on‐demand treatment, increasing the inhibitor risk. Aim: To compare the antibody response to treatment with recombinant human FVIII (rhFVIII) in relation to induced knee joint bleeds and treatment without concurrent bleeds in a HA rat model. Method: HA rats were divided into two groups: one group ( n = 10) receiving three needle induced knee joint bleeds 14 days apart and a control group ( n = 9) receiving three sham procedures. Three hours after each injury/sham 50 IU kg −1 rhFVIII was administrated intravenously. Subsequently, both groups continued rhFVIII treatment for another 9 weeks. Binding antibodies were analysed using an enzyme‐linked immunosorbent assay and neutralizing antibodies using a Bethesda‐like assay. Results: Rats in the knee‐bleed group developed a significantly faster inhibitor response and reached significantly higher inhibitor levels. In the knee‐bleed group, 80% developed inhibitors vs. 33% in the control group, demonstrating a 2.4 times higher inhibitor risk when treating concurrent with bleeds. Conclusion: FVIII treatment in relation to a bleed potentiates inhibitor development compared to FVIII treatment alone in this HA rat, indicating that bleeding is a potential danger signal. Our results support the theory that FVIII replacement therapy concurrent with a bleeding episode increases the inhibitor risk, which to the best of our knowledge, has not been confirmed in an animal model before.